Principle of Same Rights to Land in Absentee Land Ownership - Endah Kibiantiningsih; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Land is one of the natural resources in Indonesia that can be used as a means to achieve the welfare of the nation's life, so it needs state intervention to regulate it. In accordance with the constitutional mandate as stated in Article 33 Paragraph (3) of the 1945 Constitution, Act No. 5 of 1960 concerning Basic Regulations on Agrarian Principles or called the UUPA is stipulated. All kinds of land rights can be granted to all Indonesian people, both men and women, regardless of race, ethnicity and religion. From these provisions, Article 10 of the UUPA paragraph (1) stipulates that every person and legal entity that a right to agricultural land is in principle has to work or actively cultivate it himself, by preventing extortion. The article does not explicitly explain that it is prohibited to own agricultural land in an absentee manner, but this article can be intended to do so. The term absentee land will not be found in statutory regulations, but it can be understood that absentee land is land ownership located outside the area where the owner lives. Agricultural land should actually be used and worked on in an effort to meet productivity which will increase the national economy. However, the prohibition on land ownership does not apply to Civil Servants (PNS) who are equal with those who are carrying out state duties. Based on the above background, the formulation of the problem that the author wants to put forward in this study are: (1) How is the application of the principle of equality of land rights in absentee land ownership at the Karanganyar Regency Land Office. (2) Is absentee land ownership at the Karanganyar Regency Land Office in accordance with the application of the principle of equal rights to land. (3) How to obtain rights to Absentee land at the Karanganyar Regency Land Office. This study uses a normative juridical method, namely research that is fundamental in certain methods, systematics and thoughts which aims to examine one or several legal phenomena by analyzing them. From the research in the field, it can be concluded that the prohibition of absentee land ownership in Karanganyar Regency is not in accordance with the principle of equal rights between civil servants and the general public. The way to register land ownership (in this case land with the term absentee) for civil servants, as well as in Karanganyar district is (1) Applying for a permit to the local BPN office (2) Identity Card and appointment letter for PNS, TNI, POLRI (3) For retirees attach a statement letter that will manage the registered land itself. Ways to register land ownership for common citizens; (1) Identity Card, (2) Family Card, (3) Notice of Taxes Payable and (4) Land History.